The Application of the Independent Learning Curriculum As A Strengthening of the Role of Teachers In Madrasah Ibtidaiyah: A Literature Review - Putri, Julianti; Munawwarah, Al; Munira, Munira (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
The application of the Merdeka curriculum at the madrasah Ibtidaiyah level is a form of recovery from the impact of the COVID-19 pandemic, with the Merdeka curriculum aimed at allowing students to develop. Grow courage, independence, enthusiasm for learning, self-confidence, and optimism, develop freedom of thought and accept successes and mistakes. This study aims to identify the application of the curriculum in Madrasah Ibtidaiyah so that it can answer the problems of students in this day and age who are left behind with existing technology because they are confined (confined) by monotonous formal school education with learning in the classroom without direct application so that the learning obtained is only temporary knowledge and then overflows just like that. This study used a qualitative descriptive approach. The data obtained is based on literature reviews of related journals. The application of this independent curriculum is essential to be applied to current learning with the launching of the era of society 5.0, which requires humans to understand the development of the times that should not be left behind by technology so that even from MI students are expected to be able to implement the learning obtained in schools but to realize the need for educators who can innovate and create knowledge that can deliver students to HOTS (High Other Thinking Skill). Educators must now be able to understand cognitively and effectively, and psychomotor must also be considered